Al-Ushul Al-Khamsah Mutazilah dalam Pandangan KH. Mustain Syafiie: Studi Analisis di Pondok Pesantren Tebuireng Jombang - Muhammad Helmi Mighfaza; Muhlas Muhlas (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study aims to examine Ushul al-Khamsah Mutazilah (at-Tauhid, al-'Adl, al-Wad wa al-waid, al-Manzilah Baina al-Manzilatain, Amr Maruf Nahy Munkar) in the view of the Tebuireng ulama who is from the Ashariyah. The research method used qualitative with the type of field research to obtain data and kalam science as an umbrella for theory and analysis. The results and discussion of this research include the Mutazilah theology, the concept of Ushul al-Khamsah Mutazilah and the views of the Tebuireng ulama, while the ulama of Terbuireng believes that the concept of Ushul al-Khamsah in Mutazilah theology is more applicable in life and looks more at the anthropocentric side. This research concludes that the Tebuireng ulama are more personally adapted to using theology in their social and religious life in the community, judging from which it brings benefits to themselves and society.